The effect of argon cold atmospheric plasma on the metabolism and demineralization of oral plaque biofilms - Zhao, Haowei; Wang, Xu; Liu, Zhuo; Wang, Ye; Zou, Ling; Chen, Yu; Han, Qi (Frontiers in Cellular and Infection Microbiology, 2023)
Objective The aim of this study was to design and optimize a cold atmospheric plasma (CAP) device that could be applied in an oral environment and to study its effects on plaque biofilm metabolism and regrowth, as well as microbial flora composition and enamel demineralization. Method CAP was obtained through a dielectric barrier discharge device; the optical properties were analyzed using emission spectroscopy. The electrochemical analysis of plasma devices includes voltametric characteristic curves and Lissajous. The Streptococcus mutans (UA159) and saliva biofilms were treated in vitro, and the effects of CAP on biofilm metabolism were investigated using MTT and lactate dehydrogenase assays. The duration of antibacterial activity on biofilms was examined, scanning electron microscopy was used to observe the morphology of biofilms, and 16S rRNA sequencing was used to explore the influence of CAP on the microbial flora composition of saliva biofilms. An in vitro model of biofilm-enamel demineralization was designed, and the effect of CAP on enamel demineralization was evaluated by micro surface hardness and micro-CT analysis. Results CAP had antibacterial proliferative ability toward Streptococcus mutans biofilms and saliva biofilms and was stronger than ultraviolet under the same tested conditions. After 24 h, the antibacterial effect disappeared, which proved the short-term timeliness of its bactericidal ability. CAP can inhibit the acid production of biofilms, and its inhibitory effect on saliva biofilms can be extended to 24 h. CAP had a strong ability to regulate the composition of plaque biofilms, especially for Lactococcus proliferation, a major acid-producing bacterium in microcosm biofilms. The CAP-treated enamels were more acid-tolerant than non-treated controls. Conclusion CAP had an explicit bactericidal effect on caries-related biofilms, which is a short-term antibacterial effect. It can inhibit the acid production of biofilms and has a downregulation effect on Lactococcus in saliva biofilms. CAP can help reduce demineralization of enamel.